(untitled) (Nexo Revista Científica, 2023)
The paper addresses the geobotanical features of key areas along the Black Sea coast, focusing on the region from Novorossiysk to Kabardinka and from the Betta farm to Inal Bay (Russia). The study assesses the condition of plant populations, evaluates community disturbances caused by various factors, and examines vegetation patterns in relation to elevation. Of significant concern is the impact of both natural conditions and human activities on these coastal ecosystems. The paper underscores the need for effective management strategies to mitigate the detrimental consequences of human intervention and to safeguard the region’s biodiversity. The study underscores the importance of sustainable practices and eco-friendly tourism as part of responsible management approaches to maintain the appeal and ecological integrity of the Black Sea coast. In conclusion, the paper’s insights into the geobotanical aspects of the Black Sea coast offer valuable guidance for management strategies that can harmonize human activities with the protection and restoration of these vital coastal ecosystems.